2013
DOI: 10.1242/dev.100511
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of scaling in pattern formation

Abstract: Many organisms and their constituent tissues and organs vary substantially in size but differ little in morphology; they appear to be scaled versions of a common template or pattern. Such scaling involves adjusting the intrinsic scale of spatial patterns of gene expression that are set up during development to the size of the system. Identifying the mechanisms that regulate scaling of patterns at the tissue, organ and organism level during development is a longstanding challenge in biology, but recent molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
95
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 81 publications
(100 reference statements)
1
95
0
Order By: Relevance
“…Very different from these examples, it has been shown that the scaling of neural tube pattern in two birds of different size is due to a difference in the threshold at which the cells of the two species respond to signals (Uygur et al, 2016). Other examples and theoretical models exist that further explain the scaling of pattern formation in vivo (Kicheva and Briscoe, 2015;Umulis and Othmer, 2013).…”
Section: Size Control and Scalingmentioning
confidence: 98%
“…Very different from these examples, it has been shown that the scaling of neural tube pattern in two birds of different size is due to a difference in the threshold at which the cells of the two species respond to signals (Uygur et al, 2016). Other examples and theoretical models exist that further explain the scaling of pattern formation in vivo (Kicheva and Briscoe, 2015;Umulis and Othmer, 2013).…”
Section: Size Control and Scalingmentioning
confidence: 98%
“…a twofold increase in length, indicating that this mechanism is mainly based on an effective increase in the Dpp diffusion coefficient 16 . However, measurements in a range of systems, including the Drosophila wing imaginal disc, show that the (effective) diffusion coefficient of the ligand does not change, even though its gradient scales 15 .…”
mentioning
confidence: 99%
“…1b). Different models have been proposed to explain the scaling of morphogen gradients in the various systems where scaling has been analysed [9][10][11][12][13][14][15][16][17] . However, these models have remained controversial because of conflicting experimental observations 16,[18][19][20][21] .…”
mentioning
confidence: 99%
See 2 more Smart Citations